Experimental and computational investigation of building integrated PV thermal air system combined with thermal storage - Xiang, Yetao (2017)
Issues from global warming with increased CO2 emissions have been to a main concern over world. As an example in the UK, the energy demand in the domestic sector has risen by 17% in 2010 compared with that of 1970. Applying renewable energy is widely agreed to be the most effective and promising way to solve the problem where solar energy and photovoltaic technology have been greatly developing from the last century. Photovoltaic combines with Phase Change Material (PV/PCM) system is a hybrid solar system which uses phase change material to reduce the PV temperature and to store energy for other applications. This thesis aims to investigate the performance of a designed building integrated photovoltaic thermal system (BIPVT) with PCM as thermal storage for building applications. The research objectives are to increase the building integrated photovoltaic (BIPV) efficiency by incorporating PCM while utilising the stored heat in PCM for controlling indoor conditions and reduce the total building energy consumption. The research starts with solar energy convection technologies including solar thermal and solar photovoltaic. Then a combined technology named photovoltaic thermal system (PVT) was introduced and discussed. Research work on a different type of PVT using water and air as thermal energy medium was further reviewed and discussed. An analytical approach investigation was presented on a PVT system and the results were used to design the experiment work on PV/PCM configuration. Experiments have been carried out on a prototype PV/PCM air system using monocrystalline photovoltaic modules. Transient simulations of the system performance have also been performed using a commercial computational fluid dynamics (CFD) package based on the finite volume method. The results from simulation were validated by comparing with experimental results. The results indicated that PCM is effective in limiting temperature rise in PV device and the heat from PCM can enhance night ventilation and decrease the building energy consumption to achieve indoor thermal comfort for certain periods of time. An entire building energy simulation with designed PV/PCM air system was also carried out under real weather condition of Nottingham, UK and Shanghai, China. The result also shows a market potential of PV/PCM system and a payback time of 11 years in the UK condition if using electrical heater.